2020
DOI: 10.3390/agronomy10040559
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Associated with Rice (Oryza sativa L.) in Ghana: Effect of Regional Locations and Soil Factors on Diversity and Community Assembly

Abstract: Understanding the community composition and diversity of arbuscular mycorrhizal fungi (AMF) in an agricultural ecosystem is important for exploiting their potential in sustainable crop production. In this study, we described the genetic diversity and community structure of indigenous AMF in rain-fed rice cultivars across six different regions in Ghana. The morphological and molecular analyses revealed a total of 15 different AMF genera isolated from rice roots. Rhizophagus and Glomus were observed to be predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 79 publications
1
14
1
Order By: Relevance
“…The differences in the number of OTUs could be due to differences in the target regions of the nuclear ribosomal DNA (rDNA) and to DNA having been extracted from the soil, not from cassava roots. When relating this result to that of other crops such as yam, studies in other Western African countries have confirmed that AMF communities associated with one particular crop can differ strongly from one agro-ecological zone to another (Tchabi et al 2008;Sarkodee-Addo et al 2020). Similarly, the dissimilarities among AMF composition revealed in this study were further corroborated by the study of Van der Gast et al ( 2011) that observed that geological characteristics (using a 250 km distance-decay analysis) significantly influenced AMF distribution in horticultural fields across England.…”
Section: Discussionmentioning
confidence: 82%
“…The differences in the number of OTUs could be due to differences in the target regions of the nuclear ribosomal DNA (rDNA) and to DNA having been extracted from the soil, not from cassava roots. When relating this result to that of other crops such as yam, studies in other Western African countries have confirmed that AMF communities associated with one particular crop can differ strongly from one agro-ecological zone to another (Tchabi et al 2008;Sarkodee-Addo et al 2020). Similarly, the dissimilarities among AMF composition revealed in this study were further corroborated by the study of Van der Gast et al ( 2011) that observed that geological characteristics (using a 250 km distance-decay analysis) significantly influenced AMF distribution in horticultural fields across England.…”
Section: Discussionmentioning
confidence: 82%
“…2004; Sarkodee‐Addo et al . 2020). However, understanding of the composition of AMF communities colonizing grapevines is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a recent study [35] we reported that colonization intensity and taxonomic compositions of AMF in rice roots vary significantly among major rice-producing regions in Ghana, with available phosphorus found as the essential factor driving AMF community structures in rice roots. We found that certain environmental factors such as C/N, NO 3 and importantly available phosphorus influenced community structuring of AMF in rice in Ghana.…”
Section: Introductionmentioning
confidence: 89%